2010
DOI: 10.1115/1.4002056
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Transient Flow in a Centrifugal Pump During Starting Period

Abstract: Computational fluid dynamics were used to study the three-dimensional unsteady incompressible viscous flows in a centrifugal pump during rapid starting period (≈0.12 s). The rotational speed variation of the field around the impeller was realized by a dynamic slip region method, which combines the dynamic mesh method with nonconformal grid boundaries. In order to avoid introducing errors brought by the externally specified unsteady inlet and outlet boundary conditions, a physical model composed of a pipe syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 13 publications
0
55
0
Order By: Relevance
“…CFD technology had been successfully used in the transient calculation of pumps during starting and stopping periods [6][7][8][9]. With this method, not only the external characteristic but also the internal flow field could be obtained clearly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD technology had been successfully used in the transient calculation of pumps during starting and stopping periods [6][7][8][9]. With this method, not only the external characteristic but also the internal flow field could be obtained clearly.…”
Section: Introductionmentioning
confidence: 99%
“…DM method has been successfully used in transient simulation of a 2-dimensional centrifugal pump during starting period [11]. Then Li et al [7] pushed on a further application of DM method in a 3-D centrifugal pump to simulate the transient characteristic during starting period. Liu et al [6] used DM method to simulate the stopping transient process.…”
Section: Mathematicalmentioning
confidence: 99%
“…All of these studies were focused mainly on the direct influence of flow-induced vibration on internal structures; while relatively little attention has been given to indirect effects such as the impact of internal structures on the pressurized water reactor (PWR). The dynamic mesh model can be applied to determine the dynamic properties of the internal structures, as evidenced by several previous studies-many prior researchers have utilized this technique to simulate the dynamic properties of various types of fluid machineries such as valves, [11][12][13][14][15][16][17] pumps, 18,19 and more. These previous works suggest that the dynamic mesh model is well suited to analysis of a hypothetical drop accident in a PWR.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted by (Thanapandi and Prasad 1995) showed that pump behavior was disturbed during startup and stopping process. Li et al (2010) uses DSR (Dynamic Slip Region) method which are fully dynamic, closer to reality, and capable of capturing the instantaneous impeller-volute interactions. Gao et al (2013) has simulated the transient performance of the reactor coolant pump which has an excellent agreement with the Tsukamoto's experimental results.…”
Section: Introductionmentioning
confidence: 99%